2014
DOI: 10.2136/sssaj2013.09.0415nafsc
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Detrital Inputs and Roots on Carbon Saturation Deficit of a Temperate Forest Soil

Abstract: Soil C sequestration has been proposed as a tool for addressing climate change. However, models used to predict soil C sequestration do not account for C saturation and functional differences among soil C pools. In this study, we examined differences in soil C pool content of a forest soil in Pennsylvania following 20 yr of detrital manipulation (i.e., control, no roots, no leaf litter, no inputs, double leaf litter). Detrital input treatments had a highly significant (ANOVA, F = 10.6, p < 0.0001) effect on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
15
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 42 publications
3
15
0
Order By: Relevance
“…The potential to manipulate the stable C pools to offset ongoing climate change has driven extensive debate (Dungait et al, ), but the evidence thus far indicates that adding C to the most stable pools would not be straightforward (Bowden et al, ). Our results largely support this conclusion, as increasing aboveground input quantity for 20 years had no effect on soil C quantity, as had been previously reported for this site (Bowden et al, ; Crow et al, ; Mayzelle et al, ). There was also no indication that C concentration increased in any density fraction (Figure ), similar to results reported after 12 years of litter addition (Crow et al, ), or that the microbial community's catabolic profile was altered (Figure ).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…The potential to manipulate the stable C pools to offset ongoing climate change has driven extensive debate (Dungait et al, ), but the evidence thus far indicates that adding C to the most stable pools would not be straightforward (Bowden et al, ). Our results largely support this conclusion, as increasing aboveground input quantity for 20 years had no effect on soil C quantity, as had been previously reported for this site (Bowden et al, ; Crow et al, ; Mayzelle et al, ). There was also no indication that C concentration increased in any density fraction (Figure ), similar to results reported after 12 years of litter addition (Crow et al, ), or that the microbial community's catabolic profile was altered (Figure ).…”
Section: Discussionsupporting
confidence: 92%
“…Roots and their associated microbial communities drive soil aggregation and thus protection of soil C (Six et al, ), and there is evidence that root exclusion resulted in movement of C into the nonaggregated mineral fractions, potentially due to a decrease in aggregation. The soil C concentration of the no inputs treatment fine, heavy fraction increased versus the control treatment (Figure ), possibly due to a decrease in soil aggregation (not measured in this study) as observed by Mayzelle et al () in the same soil, though this was not apparent in the no roots treatment. There was also an increase in the C concentration of the coarse heavy fraction in the no roots treatment, though this was not apparent in the no inputs treatment (Figure ).…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…The light fraction (<1.85 g cm −3 ) of soil has generally been found to be the most reactive fraction to management or disturbance (Bremer et al, 1994;Liao et al, 2006;Spielvogel et al, 2006;Throop et al, 2013), although other studies have suggested that C accumulation occurs primarily in heavy-fraction, slowturnover pools (Grandy and Robertson, 2007). As expected, decreased litter inputs caused decreases in light-fraction pools, showing that this pool is more rapidly depleted than higher density fraction pools, which are composed of soil C stabilized in aggregates (intermediate density fractions) or by strong organomineral associations (heaviest fractions) (Hatton et al, 2012;Mayzelle et al, 2014). Litter additions, however, did not result in parallel increases in either total soil C or any of the density pools; rapid respiration of O or mineral soil horizon organic matter, due to enhanced microbial activity or to increased rhizospheric activity, may have prevented soil C increases (Spears and Lajtha, 2004).…”
Section: Soil Carbon Qualitymentioning
confidence: 84%
“…The response of soil organic matter (SOM) to changes in forest biomass and litter inputs might have a significant temporal lag; Holub et al (2005) found no effect of above-and belowground organic inputs on SOM in two different forest soils after 4 or 11 yr. Although most ecosystem C models assume a strong linkage between net primary productivity, litter inputs, and soil C accumulation (Gottschalk et al, 2012), soils have finite capacities to sequester C and might "saturate" or achieve maximum equilibrium levels under different combinations of soil texture, mineralogy, and climatic regimes (Chung et al, 2010;Stewart et al, 2009;Six et al, 2002;Mayzelle et al, 2014). The C saturation deficit is the difference between current C content and the point of C saturation (Hassink, 1997), and thus C accumulation potential depends on litter input rates, decomposition rates, soil mineralogy, soil C content, and soil C saturation capacity.…”
mentioning
confidence: 99%